2016
DOI: 10.3390/metabo6040044
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Implications of Glucocorticoids in a High-Fat Diet Setting and the Counter-Effects of Exercise

Abstract: Glucocorticoids (GCs) are steroid hormones, naturally produced by activation of the hypothalamic-pituitary-adrenal (HPA) axis, that mediate the immune and metabolic systems. Synthetic GCs are used to treat a number of inflammatory conditions and diseases including lupus and rheumatoid arthritis. Generally, chronic or high dose GC administration is associated with side effects such as steroid-induced skeletal muscle loss, visceral adiposity, and diabetes development. Patients who are taking exogenous GCs could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 113 publications
0
22
0
Order By: Relevance
“…Interestingly, serum corticosterone levels were not increased and oscillated normally on HFD. This is intriguing, considering associations between chronic HFD and insulin resistance of skeletal muscle and liver (Oakes et al, 1997) largely mirror metabolic complications associated with chronic glucocorticoid administration, including impaired insulin-dependent glucose uptake and metabolism by muscle, and reduced insulin-mediated suppression of hepatic glucose production leading to hyperglycemia (Dunford and Riddell, 2016). Our results indicate that chronic HFD may locally enhance sensitivity to the effects of endogenous glucocorticoids.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, serum corticosterone levels were not increased and oscillated normally on HFD. This is intriguing, considering associations between chronic HFD and insulin resistance of skeletal muscle and liver (Oakes et al, 1997) largely mirror metabolic complications associated with chronic glucocorticoid administration, including impaired insulin-dependent glucose uptake and metabolism by muscle, and reduced insulin-mediated suppression of hepatic glucose production leading to hyperglycemia (Dunford and Riddell, 2016). Our results indicate that chronic HFD may locally enhance sensitivity to the effects of endogenous glucocorticoids.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have also observed remarkable increases in the liver mass by corticosterone (CORT) treatment [ 21 - 24 ]. It is probable that increased liver mass can be caused by enhanced fatty acid synthesis and central fat deposits in the liver response to high circulating CORT levels [ 25 , 26 ]. Liver weight results found in our study are opposed to those found in another study conducted by a group of researchers [ 27 ].The relative and actual mass of the liver was significantly higher in DEX-treated chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who are taking exogenous GCs might also be more susceptible to poor food choices; however, the effect of increased fat consumption in combination with elevated exogenous GCs has only recently been investigated. 47 These studies have shown that the metabolic effects initiated through exogenous GC treatment are significantly amplified when combined with a HFD. Animal data confirm that rodents on a HFD and elevated GCs demonstrate more glucose intolerance, hyperinsulinaemia, visceral adiposity and skeletal muscle lipid deposition when compared with rodents subjected to either treatment on its own.…”
Section: Why Rheumatologists Should Care About Diet In Ramentioning
confidence: 99%